Rare Bacterial Infection of the Stomach - Hyun Myung Cho; Su Jin Kim; Jin Ook Jang; Jung Wook Lee (Yong Chan Lee, 2024)
An acidic environment, gastric emptying, and abundant blood supply inhibit bacterial infection of the stomach. Helicobacter pylori can evade these defense mechanisms and is a well-known etiological contributor to chronic gastritis. Non-H. pylori bacterial infections such as acute phlegmonous gastritis, gastric syphilis, gastric tuberculosis, and gastric actinomycosis are uncommon and owing to their nonspecific findings, are diagnostically challenging in patients without a high index of clinical suspicion. Predisposition to bacterial infection is attributable to an increase in the prevalence of medical conditions and factors that precipitate immunosuppression, in addition to high rates of gastric mucosal injury associated with endoscopic procedures. Gastric bacterial infection negatively affects patients' quality of life, increases the socioeconomic burden, and may occasionally be fatal. Therefore, physicians should be familiar with the endoscopic features and clinical manifestations of non-H. pylori bacterial infections of the stomach.